A Suitable Polysulfide Electrolyte for CdSe Quantum Dot-Sensitized Solar Cells - H. K. Jun; M. A. Careem; A. K. Arof (International Journal of Photoenergy)
A polysulfide liquid electrolyte is developed for the application in CdSe quantum dot-sensitized solar cells (QDSSCs). A solvent consisting of ethanol and water in the ratio of 8 : 2 by volume has been found as the optimum solvent for preparing the liquid electrolytes. This solvent ratio appears to give higher cell efficiency compared to pure ethanol or water as a solvent. Na2S and S give rise to a good redox couple in the electrolyte for QDSSC operation, and the optimum concentrations required are 0.5 M and 0.1 M, respectively. Addition of guanidine thiocyanate (GuSCN) to the electrolyte further enhances the performance. The QDSSC with CdSe sensitized electrode prepared using 7 cycles of successive ionic layer adsorption and reaction (SILAR) produces an efficiency of 1.41% with a fill factor of 44% on using a polysulfide electrolyte of 0.5 M Na2S, 0.1 M S, and 0.05 M GuSCN in ethanol/water (8 : 2 by volume) under the illumination of 100 mW/cm2 white light. Inclusion of small amount of TiO2 nanoparticles into the electrolyte helps to stabilize the polysulfide electrolyte and thereby improve the stability of the CdSe QDSSC. The CdSe QDs are also found to be stable in the optimized polysulfide liquid electrolyte.